Manejo ecológico de fitopatógenos em sementes de tomate - Silva, Mônica Shirley Brasil dos Santos e (2015)
The tomato crop is subject to various diseases and seeds are considered important routes of transmission of these diseases, making it necessary to treat these seeds, which is a valuable measure for reducing these pathogens. Therefore, this work aimed to evaluate the health and physiological quality of tomato seeds, as well as the methods that promote the reduction of pathogens associated with these seeds, such as the use of plant extracts (eucalyptus, cinnamon, basil and neem) chemotherapy, biological products and thermotherapy. In seed health, samples were disinfected plated and evaluated after seven days. For the transmission rate of 12 trays were prepared with 100 seeds each, in order to make up evaluations at 7, 14, 21 from where 100 seedlings were collected. The plant tissues were plated and evaluated after seven days. Aqueous extracts were prepared at a concentration of 0.5%, where the seeds were immersed for 10 min. In the control with chemical and biological products, seeds were treated in accordance with the manufacturer's recommendations. Soon after the treatments, the seeds were plated and incubated. The evaluation was carried out after seven days. In sanity test a higher incidence of Aspergillus fumigatus (26%) and Aspergillus flavus (26%) in seeds of tomato varieties Ipa 6 and San Marzano, respectively. Quantification of transmission were detected fungi A. flavus, A. fumigatus, A. niger, A. stolonifer and Curvularia sp. for seed of varieties San Marzano tomatoes and Ipa 6. The plant extract which enabled lower average incidence of fungi in tomato seeds 'San Marzano' was the basil and in the 'Ipa 6' was the Eucalyptus. Treatment with chemical and biological products, and Carbendazin Thiofanato Methyl fungicides and the biological product Quality®, were those with an average incidence of 0.00 colonies / treatment, seeds of two varieties of tomato. In thermotherapy of tomato seeds, treatments that are highlighted with an average incidence of 0,00 colonies / treatment were 50 ° C / 30 min and 55 ° C / 25 min for the range San Marzano and the IPA variety 6 , all treatments 14 showed no incidence in seeds. It was observed that most of the treatments did not interfere negatively on germination of seeds of two varieties of tomato. There was a reduction of pathogens in treated seeds can be inferred that the treatments have the potential to control plant pathogens and thus is an alternative to chemicals. However, the effect of the treatments is differentiated in accordance with the pathogen